2021
DOI: 10.1101/2021.08.06.455454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal-hypothalamic circuit controls context-dependent innate defensive responses

Abstract: Preys use their memory - where they sensed a predatory threat and whether a safe shelter is nearby - to dynamically control their survival instinct to avoid harm and reach safety. However, it remains unknown which brain regions are involved, and how such top-down control of innate behaviour is implemented at the circuit level. Here, we show that the anterior hypothalamic nucleus (AHN) is best positioned to perform this task as an exclusive target of the hippocampus (HPC) within the medial hypothalamic defense … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
(91 reference statements)
2
6
0
Order By: Relevance
“…Several previous studies that directly examined the effect of stimulating or inhibiting AHN neurons have yielded contradicting results. While some of them concluded that AHN stimulation cause escape response (Bang et al, 2022; Wang et al, 2015), others suggested the opposite (Anthony et al, 2014). Yet, none of these studies examined the role of the AHN in a social context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies that directly examined the effect of stimulating or inhibiting AHN neurons have yielded contradicting results. While some of them concluded that AHN stimulation cause escape response (Bang et al, 2022; Wang et al, 2015), others suggested the opposite (Anthony et al, 2014). Yet, none of these studies examined the role of the AHN in a social context.…”
Section: Discussionmentioning
confidence: 99%
“…The AHN is a relatively understudied and poorly defined brain area, known as part of the medial hypothalamic defensive system (Canteras, 2002). It includes mainly inhibitory GABAergic neurons (Bang et al, 2022; Wang et al, 2015; Xie et al, 2022) which largely project to several brain regions thought to be central to fight-or-flight behavior, such as the lateral septum (LS) and dorsal periaqueductal gray (dPAG) area (Risold et al, 1994; Xie et al, 2022). In rats and mice, the AHN was shown to take part in responses to predators (Cezario et al, 2008; Martinez et al, 2008; Mendes-Gomes et al, 2020) as well as in regulating parental behavior (Tachikawa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that contextual learning influences AHA neuronal activity in part through hippocampal inputs that enhance goal-directed escape behavior 7 . Therefore, we first investigated whether a classic foot shock-cue conditioning paradigm modulates AHA neuronal activity.…”
Section: Foot-shock Conditioned Auditory Cues Evoke An Increase In Ah...mentioning
confidence: 99%
“…Robust escape behaviors such as increases in locomotor activity and jumping were triggered by the activation of the VMH→AHA pathway 6 . Moreover, activation of hippocampal inputs to the AHA promotes contextual control of such behaviors 7 . Thus, these findings raise questions about the etiological role of AHA neuronal activation in stress-related and compulsive disorders 8 .…”
Section: Introductionmentioning
confidence: 99%